The Posttraumatic Proximal Cross-union of the Forearm in Childhood: What is Recommended? - Dudda, Marcel (PAGEPress, 2013)
The posttraumatic proximal cross-union of the forearm in childhood is a rare complication after radial head, neck or proximal forearm fractures and elbow dislocations. There is no standardized treatment. Several surgical procedures with or without interposition techniques are described in the literature. The aim of this study was to analyze all children with cross-unions who underwent surgery over the last 15 years. From 1998 to 2013, 8 children with a posttraumatic proximal cross-union of the forearm (Type 3 according to Vince and Miller) received surgical treatment with resection of the cross-union or radial head. Mean age at the time of initial trauma was 9.0±2.56 years (range 6-14 years), age at the time of surgery was 11.9±3.09 years (range 7-16 years). Mean time of resection of the crossunion was 23.2 months. Follow-up time was 10.6 months (range 1-36 months). Five patients had a resection of the cross-union without any interposition techniques, in 2 cases with an additional arthrolysis of the elbow. One patient had an interposition of a local fascia flap. In 2 cases, a primary excision of the radial head, six and seven years, respectively, after trauma, was performed. All patients, except one, had non-steroidal antiinflammatory drugs therapy after surgery. A post-operative irradiation was performed in 3 cases. The mean postoperative range of motion for pronation/supination was 36/0/53°. Controversy remains about the best procedure to adopt for posttraumatic cross-union in childhood. After analysis of our data and the literature, we recommend the resection of the crossunion within 6-24 months of occurrence without necessarily using any interposition techniques. All patients reported an improvement with regard to ordinary activities. In cases of long-term cross-union for several years with ankylosis of the elbow and bony deformities of the proximal radius, an excision of the radial head as salvage procedure is recommended.